TWO WAVELENGTHS DEPENDENT SPECTROPHOTOMETRIC METHODS FOR QUANTITATIVE ESTIMATION AND VALIDATION OF OXFENDAZOLE IN PRESENCE OF ITS ALKALI-INDUCED DEGRADATION PRODUCT: A COMPARATIVE STUDY - Madkour, Ahmed (Innoriginal: International Journal of Sciences, 2017)
Four simple, accurate, selective, reproducible and sensitive spectrophotometric methods, each method based on selection of two wavelengths, have been developed and validated for the determination of oxfendazole in the presence of its alkali-induced degradation product without preliminary separation. These methods include (A) dual wavelength method at 291.6 and 304.9 nm, (B) Q-analysis method at 275.5 and 292 nm, (C) simultaneous equation method at 292 and 299 nm and (D) absorbance ratio method at 275.5 and 292 nm. These methods were validated and successfully applied for determination of oxfendazole in UnifendazoleÂ® suspension. The obtained results were statistically compared with those of the reported method by applying t-test and F-test at 95% confidence level and no significant difference was observed regarding accuracy and precision.Â 